Rancang Bangun Indikator Emergency Stop Pada Conveyor Kedatangan Internasional Di Bandar Udara Internasional Jenderal Ahmad.pdf - Samudera Novarizki, Muhammad; Fatra, OKa; Wahid Alfaritzy, Nurdin; Restu, Aldo; Ardiansyah, Mohammad; Arifin, Taufiqurrahman (Jurnal Teknik Mekanikal Bandar Udara, 2024)
Ahmad Yani International Airport has a Baggage Handling System which is a conveyor that has an automatic system to transport luggage from the check-in counter to the plane or from the plane to the passenger. However lack of response time when the emergency stop is pressed which can result in baggage accumulation and overload on the motor, without an emergency stop indicator and the number of emergency stop push buttons is more than one, making it difficult for technicians and takes a lot of time to find a pressed emergency stop. To be effective, it is necessary to design an emergency stop light indicator. By adding wiring that is connected to each emergency stop to provide input to the emergency stop lamp so as not to manually search for the emergency stop button that is pressed